DIFFICULTIES IN TEACHING ENGLISH PRONUNCIATION TO IT STUDENTS (Journal of Universal Science Research, 2024)
Since English is a universal language, learning the language has become a trend. Nevertheless, after spending a great deal of time studying, a lot of students still struggle with English pronunciation. They frequently miss the mark while communicating in English, and vice versa—people are unable to comprehend what native speakers are attempting to communicate.